Introduction to biblical interpretation - Klein, William W. (William Wade); Blomberg, Craig L.; Hubbard, Robert L., Jr. (Grand Rapids, Michigan : Zondervan, 2017)
Introduction to Biblical Interpretation, now in its third edition, is a bestselling hermeneutics textbook that sets forth concise, logical, and practical guidelines for discovering the truth in God's Word. With updates and revisions throughout that keep pace with current scholarship, this book offers students the best and most up-to-date information needed to interpret Scripture.
Application
Includes bibliographical references and index.
Keywords: Bible -- Hermeneutics